Carers' and service users' experiences of early intervention in psychosis services: implications for care partnerships. Issue 3 (13th January 2016) - Allard, Jon; Lancaster, Susan; Clayton, Sara; Amos, Tim; Birchwood, Max
Abstract: Aim: To explore carers' and service users' experiences of UK Early Intervention Services following referral for first‐episode psychosis. Methods: Thirty‐two semi‐structured interviews (16 interviews with service users and 16 corresponding interviews with their carers) were completed and analysed. Results: Carers spoke retrospectively and prospectively by framing their accounts into the periods before and since their engagement with Early Intervention Services. Desperation was evident as emotive experiences were recalled prior to referral. Relief then emerged as carers described support and engagement with key workers. Hope and optimism for the service user's prognosis and life trajectory were also expressed.Service users described similar positive experiences of Early Intervention Services and the support and insight they had gained through their relationships with key workers. They were however less focused on accounts of desperation and relief and more immersed in their current understanding and attempts to normalize their experiences of first‐episode psychosis. Prognosis and future trajectories were only discussed tentatively. Conclusion: Communication and 'partnerships' with service users and carers are essential for effective service engagement, delivery of care and the reduction in relapse following first‐episode psychosis. This study highlights how key workers from Early Intervention Services are appropriately valued and situated to develop such relationships. Findings also reveal that service users' and carers' focus and expectations of recovery vary during the early stages of engagement with services. How key workers manage awareness and communication around such differing expectations is a crucial consideration for maintaining the 'partnerships' necessary for effective service provision.